Pengembagan Sistem Informasi Administrasi dan Rencana Aktivitas Belajar untuk TK Darussalam Plus - Affan taufiqur Abroor; Mulyati Sri (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
In the era of digital transformation, more and more institutions are taking advantage of this technological development. In the field of education, the use of digital transformation can be found in many places, such as the use of websites and applications to make it easier for teachers to view teaching schedules, and students and the public can also access school information quickly and easily. This study discusses the development of a website-based information system to make it easier for teachers at TK Darussalam Plus to solve the problems they face, namely the data collection of school administration and learning activity plans that are still using paper and books, and some data is stored using the Excel application. The use of these two systems causes the data to be not organized neatly, some data is in the book, and some data is in the Excel, which causes the search and management of data to be inefficient and ineffective.To overcome this problem, an information system was built using the agile development method, which is one of the application development methods that is flexible to changes that occur during system development. Based on the results of the UAT test that has been carried out, this information system has obtained satisfactory results with a value of 77% in the attractiveness section, 97% in the learnability section, 75% in the operability section, 90% in the understandability section, the website-based information system that has been developed is a solution that meets the needs required by the TK Darussalam Plus.